Economic development in Ceylon - Karunatilake, H. N. S. (New York : Praeger Publishers, 1971)
This book examines the developmental problems in numerous sectors of the Ceylon (now Sri Lanka) economy, surveys governmental policies in each, and describes in some detail the legislation, incentive systems, and institutions established in an effort to promote economic growth. It is a study of how policy looks from the highest level.
Includes bibliographical reference: p. 369-378.
lje 08/10/2018
Loans
Keywords: Economic development; Economic growth; Sri Lanka